Laparoscopic Natural Orifice Specimen Extraction Surgery versus Conventional Surgery in Colorectal Cancer: A Meta-Analysis of Randomized Controlled Trials - Zhuqing Zhou; Lin Chen; Jie Liu; Fang Ji; Yuanyuan Shang; Xudong Yang; Yao Yang; Chuangang Fu (Gastroenterology Research and Practice)
Objective. This study was to quantitatively synthesize data in randomized controlled trials (RCTs) of laparoscopic resection comparing natural orifice specimen extraction (NOSE) versus conventional laparoscopy (CL) in colorectal cancer. Methods. We identified eligible RCTs by searching seven electronic databases (PubMed, Cochrane Library, Embase, Web of Science, CNKI, CQVIP, Wanfang, and Sinomed). Mean differences (MDs) between groups with 95% confidence intervals (CIs) were used for continuous outcomes. Event rate ratios (RRs) were also calculated with their 95% CIs. Results. 1,569 citations were identified from electronic database as of June 2020, and finally, 21 RCTs involving 2,112 patients met the study eligibility criteria and were included. Compared to the CL group, NOSE had longer operation time (MD: 8.14 min, 95% CI: 3.02 to 13.25, and p<0.01), less estimated blood loss (-10.64 ml, 95% CI: -14.92 to -6.36, and p<0.01), less hospital stay after surgery (-2.21 days, 95% CI: -3.36 to -1.06, and p<0.01), shorter time of gas passage after surgery (-0.58 days, 95% CI: -0.82 to -0.34, and p<0.01), better pain score (-1.06, 95% CI: -3.74 to -0.37, and p<0.01), and improved cosmetic scores (1.93, 95% CI: 0.77 to 3.10, p<0.01). Rate ratios of total complications, infection, and incision infection all favored NOSE surgery, with RRs (95% CIs) of 0.81 (0.71 to 0.93), 0.34 (0.21 to 0.54), and 0.24 (0.12 to 0.51), respectively. Conclusion. This report appeared the first comprehensive meta-analysis of RCTs to synthesize data of laparoscopic resection with NOSE versus conventional laparoscopy. NOSE surgery seemed favorable with shorter hospital stay, less pain score, a shorter time to recover along with better cosmetic scores, and less postoperative complications.